Some anatomical details of female genitalia observed in Malthodes parthenias Kiesenwetter (Coleoptera Cantharidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Internal genitalia were studied on fresh material of both sexes. Spermatheca is a vesicular, unpaired organ; it was recognized from its steady content of sperm in all examined females (n=15); it connects by an integumental filament to another unpaired, vesicular organ. The latter can't be regarded as copulatory pouch, because of the absence of phallic intromittent structures in the male of the same species; on the contrary, it exhibits some features of a colleterial gland, as it is provided of: (a) a swelling reservoir, (b) a secretary diverticulum, ( c) a long duct leading to the vagina. Connection between the spermatheca and the colleterial gland is merely a mechanical one, as it doesn't include a duct. According to the literature, female genitalia of certain Malthodes are analogous to those of Lepidoptera Ditrysia: however, this analogy doesn't exist in M. parthenias, owing to the lack of both a double genital opening and a supplementary duct for sperm passage.
Keywords: spermatheca; unpaired colleterial gland; Lepidoptera Ditrysia; supposed analogy